The emergence of emotions and pro-social and religious sentiments during the September 11 disaster - David A. Savage; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2011)
Analysing emotional states under duress or during heightened, life-and-death situations is extremely difficult, especially given the inability of laboratory experiments to adequately replicate the environment and the inherent biases of post event surveys. It is in this area that natural experiments come to the fore by combining the randomization that comes from natural data with an experimentally realistic event. The pager communications from September 11th, made publicly available by Wiki Leaks (Wiki Leaks, 2009), provide exactly the kind of natural experiment emotion researchers have been seeking. We have analysed the pager messages by applying an absolute count methodology and by presenting both positive and negative emotive categories as well as the development of pro-social and religious sentiment. Providing behavioural evidence on how people communicate under extreme circumstances and offers valuable insights into human nature. We demonstrate that positive and pro-social communications are the first to emerge followed by the slower and lower negative communications. Religious sentiment is the last to emerge, as individual attempt to make sense of event.
Keywords: D03; D70; D64; Z12; N30; Z10; 330; Content Analysis; Positive Emotion; Negative Emotion; Religiosity; Disaster Communications; 9/11